2015
DOI: 10.1080/09613218.2015.1045702
|View full text |Cite
|
Sign up to set email alerts
|

The home as enabler of more active lifestyles among older people

Abstract: Inactive lifestyles have negative health consequences, while time spent sedentary (sitting and lying) is related to morbidity and premature mortality. Older adults often form the most sedentary segment of the population. Much of this behaviour may be practised at home where this group can spend extended periods. Physical activity rates among older adults are particularly low. Even household physical activities can be beneficial for this group, while they can constitute much of an older person's total activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 78 publications
1
32
0
1
Order By: Relevance
“…Such environments were welcomed. Other research with stroke survivors has found a similar interest in spacious environments (Brookfield et al 2015). Unmade paths proved problematic and hindered the progress of individuals with mobility impairments.…”
Section: Popular Destinationsmentioning
confidence: 94%
See 3 more Smart Citations
“…Such environments were welcomed. Other research with stroke survivors has found a similar interest in spacious environments (Brookfield et al 2015). Unmade paths proved problematic and hindered the progress of individuals with mobility impairments.…”
Section: Popular Destinationsmentioning
confidence: 94%
“…The characteristics, advantages and limitations of the focus group method have been well documented (Brookfield, Bloodworth, and Mohan 2013;Krueger and Casey 2000). Although a verbal method, and conscious of the potential for verbal communication difficulties post stroke, the successful use of focus groups in previous studies with persons with experience of stroke, including stroke survivors (Brookfield et al 2015;damush et al 2007;Sarre et al 2014) and members of stroke clubs (Ch'ng, French, and Mclean 2008;Lennon et al 2013), helped prompt their use. Further, as a qualitative method, focus groups are appropriate for accessing and understanding personal perspectives and experiences, the interest of the research.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…too high to grab or too far to reach). For example, stroke survivors with visual impairments struggle to judge stair heights and the distance between objects (Brookfield, et al, 2015). Furthermore, slippery surfaces were found to be barriers for the rehabilitation process as they obstruct patients' ability to safely move within the home setting (Zhang, et al, 2016).…”
Section: Architectural Featuresmentioning
confidence: 99%